TIME DELAY ANALYSIS ON THE AYSHA CIBINONG ISLAMIC HOSPITAL PROJECT - Muhammad Valerio Rejeki (LPPM Universitas Negeri Jakarta, 2022)
Currently, the progress of infrastructure in Indonesia is very rapid, in its implementation the project must be in accordance with the planned time. Therefore there must be project control in terms of performance in terms of the amount of work time. The purpose of this study is to find out how long the delay is on the project and how long the work is completed with the conditions that occur in the field. In the construction project of the Aysha Cibinong Islamic Hospital, West Java, there was a delay from the plan that was supposed to be completed in mid-2021, but must be completed by the end of 2021. This was due to the previous contractor having problems, therefore the implementation of this project was in Take Over which resulted in project completion delay. The method used is the concept of Earned Value Analysis (EVA) to find out how much time the project delay is estimated to be. The budget plan is Rp.9,400,000,000 (nine billion four hundred million rupiah), the planning time is 90 calendar days, while the estimated time for completion of the project or Time Estimate which is influenced by the implementation of project work on the 8th week evaluation is 90 calendar days.